A casa e o quartel: uma análise antropológica sobre o exército e a família na Academia Militar das Agulhas Negras - Silva, Cristina Rodrigues da (Universidade Federal de São Carlos, 2010)
The dissertation aims to accomplish an anthropological analysis on the family of the militaries. It seeks to understand the peculiar relationship between Army and Family, in which the very idea of Military Family indicates sometimes the military contingent of the institution; or the family in its private meaning (spouse and children) and sometimes all these elements together. An ethnographic research was carried out in Aman (Military Academy of the Agulhas Negras an institution of the Brazilian Army) and in its respective village between 2007 and 2008, where interviews were performed with couples that are configured in three different ways of family: couples in which only the husband is a military; couples in which both husband and wife are militaries and couples in which only the wife is a military. It is shown that the life of the family is linked to the military occupation of the spouse, in such a way that there is an expected military family model , being operated (to some extent) by the Army and that reflects, in particular, the case of the families in which only the husband is a military. The other familial forms present some tensions to this native model, where the main disruption occurs on the configuration of the woman s gender. Still, there seems to be "adjustments" to the native model and these new arrangements remain tied to the military life. It investigates cases of formal regulation, exchange relationships (principles of unity and solidarity among the families), social constraints (surveillance and gossip), and finally the construction of an entire symbolic apparatus, in which the Army maps roles, obligations and benefits of the officers families. Thus, it is apparent that the Army embraces the families. However, it is also pointed out that there is a double movement between home (here understood as the family of the military - spouses and children relationship, and close relatives) and barracks (relations of the military bases). Not only the barracks determines the relations in the house, but also the house determines the relations in the barracks.
Keywords: Família; Militares; Gênero; Antropologia; Militaries; Family; Gender; Anthropology; CIENCIAS HUMANAS::ANTROPOLOGIA